Tinnitus in Elderly Individuals: Discomfort and Impact in the Quality of Life - Teixeira, Adriane Ribeiro; Rosito, Leticia Petersen Schmidt; Gonçalves, Andréa Kruger; Nunes, Michelle Gassen Paulo; Dornelles, Silvia; Olchik, Maira Rozenfeld (International Archives of Otorhinolaryngology, 2017)
Introduction Tinnitus is a symptom that affects mainly the elderly and can negatively influence their quality of life.Objective The objective of our study is to evaluate the existence of a relationship between the quality of life and the impact caused by tinnitus in elderly individuals, considering the age and gender variables.Method We conducted a cross-sectional study in elderly people of both genders who participate in the extension activities at the university. The evaluation was composed of anamnesis and WHOQOL-OLD instruments, to evaluate the quality of life, and Tinnitus Handicap Inventory (THI) for the evaluation of the tinnitus impact.Result We evaluated 36 elderly individuals with an average age of 68.6 ± 6.8 years old, 72.2 % of them were women. We verified that most of the subjects classified their tinnitus as weak (44.4%) or medium (36.1%). The score average in the THI was 20 points, with predominant classification of tinnitus impact as negligible (41.7%) or mild (30.6%). In the WHOQOL-OLD, the average score was 15.6 ± 1.6 points (total score). The negative correlation between the THI score and the WHOQOL-OLD score was found in the sensory domain operation and total score.Conclusion The results obtained in the study prove that the quality of life of the elderly individuals evaluated is related to a discomfort caused by the tinnitus.
Keywords: tinnitus; elderly; quality of life; questionnaires